Implementation of Waterfall Method to Build an Online Badminton Court Booking Application in Purwakarta - Prasetio, Bayu; Alam, Syariful (RISTEC : Research in Information Systems and Technology, 2024)
The Siti Sofiah Sports Hall (GOR) is one of the buildings that rents out facilities for badminton or badminton sports. The ordering or field booking process can be done via telephone, WhatsApp application, or by visiting the location directly. Before making an order, customers first ask about the available fields and sessions on the desired day. The large number of enthusiasts who place orders or field bookings and also recording orders manually often results in recording errors or in one session there is more than one customer ordering in the same field. Based on this, GOR Siti Sofiah needs a field booking application that can make it easier for consumers to see empty schedules and also make the booking process easier. In this research, a web-based application will be built by implementing one of the software development methods, namely Waterfall Method. By building this application, the field ordering process can be better organized and also make things easier for customers and court admins.